2021
DOI: 10.14739/2310-1210.2021.1.224932
|View full text |Cite
|
Sign up to set email alerts
|

Study of the qualitative composition and quantitative content of some groups of BAS in dietary supplements with green tea leaf extract

Abstract: Recently, there has been a high demand from the population for dietary supplements that have antioxidant activity. First of all, these are dietary supplements with green tea leaf extract, because green tea contains catechins in a fairly high amount. Nowadays, according to the current legislation of Ukraine the qualitative composition and quantitative content of biologically active substances in dietary supplements are not established, which to a certain extent affects the quality and safety of these products. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In our previous research [8], the total content of catechins was established by absorption spectrophotometry. It was found that the total content of catechins was 146.80 ± 1.36, 79.0 ± 0.88, 28.0 ± 0.75 mg in DS1, DS2, and DS3, respec tively.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research [8], the total content of catechins was established by absorption spectrophotometry. It was found that the total content of catechins was 146.80 ± 1.36, 79.0 ± 0.88, 28.0 ± 0.75 mg in DS1, DS2, and DS3, respec tively.…”
Section: Resultsmentioning
confidence: 99%
“…The powder of a crushed tablet and the capsule contents of dietary supplements were completely dissolved in 96 % ethanol and filtered into a 25.0 mL volumetric flask, and diluted to the volume with the same solvent. The mobile phase was hydrochloric acid -formic acidn-butanol (16 : 19 : 65) for detection of anthocyanins [16], toluene -acetone -formic acid (9 : 9 : 2) for catechins [17], ethyl acetate -glacial acetic acid -formic acid -water (100 : 11 : 11 : 26) for flavonoids and phenolic acids [18]. The following standard solutions were used: 0.1 % cyaniding-3-glucoside and 0.1 % pelargonidin-3-glucoside (for anthocyanins); 0.25 % epicatechin and 0.1 % epigallocatechin-3-O-gallate (for catechins); 0.25 % rutin, 0.1 % chlorogenic acid, 0.01 % ellagic acid and caffeic acid (for flavonoids and phenolic acids).…”
Section: Tlc Analysis Assaymentioning
confidence: 99%
“…Nowadays, analytical methods, such as ion chromatography [11], high performance liquid chromatography-ultraviolet detection (HPLC-UV) [12], capillary electrophoresis [13], photocolorimetry [14], UV-spectrophotometry [15] and thin-layer chromatography [16], are commonly applied to analyze catechins.…”
Section: Introductionmentioning
confidence: 99%